Challenges In Online Learning Assessment During The COVID-19 Pandemic - Rahman, M Arinal; Novitasari, Della; Handrianto, Ciptro; Rasool, Shahid (Universitas Negeri Padang, 2022)
Assessment is a fundamental aspect of student learning instruction. Many challenges and problems exist in assessing students due to the online learning environment during Covid-19 pandemic. This study was investigated the Speaking II online course at English Education Department in UIN Antasari Banjarmasin. This study uses the case study research method. The research was held in two phases, and the first phase is reviewing the Speaking II online course syllabus to discover the types of assessment being used to assess student learning. Two kinds of assessments emerged: (1) role play and (2) presentation. The second phase is interviewing with the lecturer of the online course to get information about challenges and problems that arose due to physical distance between the lecturer and students. The challenges are (1) the impact of physical distance between lecturer and students, (2) Adaptations resulting from the use of technology for learning (3) Workload and time management. The study concludes with suggestions and recommendations synthesizing the results with those found in the literature.